Novel effects of statins on cancer via autophagy (2023)
Cancer is one of the main causes of death globally. Most of the molecular mechanisms underlying cancer are marked by complex aberrations that activate the critical cell-signaling pathways that play a pivotal role in cell metabolism, tumor development, cytoskeletal reorganization, and metastasis. The phosphatidylinositol 3-kinase/protein kinase-B/mammalian target of the rapamycin (PI3K/AKT/mTOR) pathway is one of the main signaling pathways involved in carcinogenesis and metastasis. Autophagy, a cellular pathway that delivers cytoplasmic components to lysosomes for degradation, plays a dual role in cancer, as either a tumor promoter or a tumor suppressor, depending on the stage of the carcinogenesis. Statins are the group of drugs of choice to lower the level of low-density lipoprotein (LDL) cholesterol in the blood. Experimental and clinical data suggest the potential of statins in the treatment of cancer. In vitro and in vivo studies have demonstrated the molecular mechanisms through which statins inhibit the proliferation and metastasis of cancer cells in different types of cancer. The anticancer properties of statins have been shown to result in the suppression of tumor growth, the induction of apoptosis, and autophagy. This literature review shows the dual role of the autophagic process in cancer and the latest scientific evidence related to the inducing effect exerted by statins on autophagy, which could explain their anticancer potentia.